Stopenjsko besedotvorje Na primeru glagolov čutnega zaznavanja - Kern, Boris (Lingua Slovenica, 2017)
This monography entitled The Multistage Word Formation (Case Study of the Verbs of Sense Perception) presents the word-formation and content-formation capabilities of verbs that denote perception of the five senses: sight, hearing, smell, touch and taste. The standpoint is based on a multistage method that extends research of the binary relation between the motivating and the motivated word into research of the relation between a non-derivative word and all of its direct and indirect derivatives.